2010
DOI: 10.1503/cmaj.100018
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Pseudomonas chondritis after piercing of the upper ear

Abstract: Contributors: All of the authors contributed substantially to the drafting of the article and approved the final version submitted for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…A total of 29 articles met inclusion criteria for this systematic review (Fig. ), and 66 patients were included in the pooled analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 29 articles met inclusion criteria for this systematic review (Fig. ), and 66 patients were included in the pooled analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, mean symptom duration was 26.0 ± 29 days, and the median was 15 days (range: 2–120 days; an outlier of 1,450 days was excluded from the analysis). Many studies (n = 26) reported symptom duration prior to patients seeking medical attention . The mean duration of symptoms prior to patients seeking medical attention was 6.2 ± 5 days, and the median was 6 days (range: 2–17.5 days).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed-Jushuf et al [41] Abscess Mycobacterium fortuitum Horii and Jackson [42] Auricular chondritis and perichondritis Lactobacillus spp. Razavi and Schilling [43] Pseudomonas aeruginosa Keene et al d [44] Lee and Gold [45] Sandhu et al [46] Fisher et al d [47] More et al [48] Turkeltaub and Habal [49] Stewart et al [50] Nonmenstrual toxic shock syndrome…”
Section: Allergiesmentioning
confidence: 99%
“…Simple tears can be sutured under local anesthesia; however, larger defects may require reconstructive surgery. [45,46] Both chondritis and perichondritis have been reported. [41] Transcartilaginous piercings may be complicated by hematoma formation, which may result in cartilage ischemia or a severe deformity commonly referred to as 'cauliflower ear.'…”
Section: Earmentioning
confidence: 99%